Characterization of EhaJ, a New Autotransporter Protein from Enterohemorrhagic and Enteropathogenic Escherichia coli - Easton, Donna M.; Totsika, Makrina; Allsopp, Luke P.; Phan, Minh-Duy; Idris, Adi; Wurpel, Daniël J.; Sherlock, Orla; Zhang, Bing; Venturini, Carola; Beatson, Scott A.; Mahony, Timothy J.; Cobbold, Rowland N.; et al. (Frontiers in Microbiology, 2011)
Enterohemorrhagic Escherichia coli (EHEC) and enteropathogenic E. coli (EPEC) are diarrheagenic pathotypes of E. coli that cause gastrointestinal disease with the potential for life-threatening sequelae. While certain EHEC and EPEC virulence mechanisms have been extensively studied, the factors that mediate host colonization remain to be properly defined. Previously, we identified four genes (ehaA, ehaB, ehaC, and ehaD) from the prototypic EHEC strain EDL933 that encode for proteins that belong to the autotransporter (AT) family. Here we have examined the prevalence of these genes, as well as several other AT-encoding genes, in a collection of EHEC and EPEC strains. We show that the complement of AT-encoding genes in EHEC and EPEC strains is variable, with some AT-encoding genes being highly prevalent. One previously uncharacterized AT-encoding gene, which we have termed ehaJ, was identified in 12/44 (27%) of EHEC and 2/20 (10%) of EPEC strains. The ehaJ gene lies immediately adjacent to a gene encoding a putative glycosyltransferase (referred to as egtA). Western blot analysis using an EhaJ-specific antibody indicated that EhaJ is glycosylated by EgtA. Expression of EhaJ in a recombinant E. coli strain, revealed EhaJ is located at the cell surface and in the presence of the egtA glycosyltransferase gene mediates strong biofilm formation in microtiter plate and flow cell assays. EhaJ also mediated adherence to a range of extracellular matrix proteins, however this occurred independent of glycosylation. We also demonstrate that EhaJ is expressed in a wild-type EPEC strain following in vitro growth. However, deletion of ehaJ did not significantly alter its adherence or biofilm properties. In summary, EhaJ is a new glycosylated AT protein from EPEC and EHEC. Further studies are required to elucidate the function of EhaJ in colonization and virulence.